An investigation into the relationship between pre-competition mood states, age, gender and a national ranking in artistic gymnastics - Boldizsar, D.; Soos, I.; Whyte, I.; Hamar, P. (Journal of Human Kinetics, 2016)
This study investigated the relationship between pre-competition mood state factors in gymnastics by gender, age and a national ranking. Participant-gymnasts (total n=116, male n=49, female n=67) completed a Brunel Mood Scale (BRUMS) one day prior to their main competition of the year. Information was also gathered from gymnasts of gender, age and a national ranking. Consistent with theoretical predictions, results confirmed that a number of pre-competition mood states differed by age with both juniors and seniors having a higher level of anger than children (p<.05 respectively). Also, seniors demonstrated higher tension than children (p<.001). However, only anger showed significant differences by gender with male gymnasts demonstrating higher levels of anger than female gymnasts (p<.05), and with international gymnasts registering higher levels of anger compared with second class gymnasts (p<.05). Authors suggest that future research should investigate relationships between the pre-competition mood in other gymnastics-related disciplines and sports, as well as competitive performances.